دور القانون الجنائي الدولي في مكافحة جريمة القرصنة البحرية - رضا، رشا ظافر محي الدين عبد (الجامعة المستنصرية - كلية القانون, 2021)
إن جريمة القرصنة البحرية كانت منذ القدم ظاهرة تهدد الأفراد وتهدد أيضا التجارة ما بين الدول وكذلك توثر على الحياة السياسية والأمنية للدول بصورة عامة. ومع تطور الأحداث أدت إلى ازدياد خطر انتشار هذه الجريمة والتي تعد من أكبر وأكثر المشاكل تهديدا لأمن وسلامة الملاحة البحرية في سواحل الدول الأفريقية والتي أثرت بدورها على حركة التجارة الدولية وأصبحت في الوقت الحاضر تلقي بأثارها الخطيرة على المجتمع الدولي ككل وقد مهدت العديد من العوامل لسرعة انتشار هذه الظاهرة (الجريمة) وهذا ما معناه أن المجتمع الدولي قد شعر بشكل جدي وفعلي بمدى الخطر الذي يحدق به وإنه أحس بضرورة وجود جهود إقليمية ودولية مشتركة للتحرك السريع لمواجهة هذه الجريمة الخطيرة فعلا على الأمن والسلم الدوليين. إن هذه الجريمة سوف تزداد أخطارها على الدول والمجتمعات الإنسانية كافة فهي لم تعد تقلق أجهزة الدولة فقط وإنما أصبحت من المعضلات الخطيرة التي تواجه المجتمع الدولي في هذه المرحلة بغض النظر عن طبيعة النظام السياسي للدول ودرجة تطورها وباعتبار إن المنظمات الإجرامية تعمل على استخدام أساليب غير تقليدية في عملياتها أي القرصنة البحرية والسطو المسلح وتتكيف مع الواقع الاقتصادي والسياسي الجديد مستغلة فتح الحدود أمام التجارة الحرة والاقتصاد العالمي. وهذا يعني إنه لا بد من إيجاد الحلول المناسبة للتقليل من أثر هذه الجرائم ومعالجتها بكافة الوسائل والأساليب الدولية من خلال التعاون ما بين الدول من خلال تقوية الحراسات وتشديدها على الحدود وهو بدوره سوف يقلل من حدة انتشار هذه الجريمة بشكل أكبر من خلال عقد الاتفاقيات والمعاهدات التي تعمل بشكل أمني مشدد بأساليب تدعو للقضاء على القراصنة والقرصنة." The crime of maritime piracy was long ago a phenomenon threatening individuals and also threatening trade between countries as well as affecting the political and security life of countries in general. With the development of events, it led to an increased risk of the spread of this crime, which is one of the biggest and most threatening problems to the security and safety of maritime navigation on the coasts of African countries, which in turn affected the international trade movement and at the present time it has had dangerous effects on the international community as a whole. Many factors have paved the way for the rapid spread of This phenomenon (crime) and this means that the international community has seriously and realistically felt the extent of the danger that threatens it, and it has felt the need for joint regional and international efforts to move quickly to confront this really dangerous crime against international peace and security. This crime will increase its dangers to all states and human societies, as it no longer only worries the state apparatus, but rather has become one of the serious dilemmas facing the international community at this stage regardless of the nature of the states' political system and the degree of its development and considering that criminal organizations are working to use unconventional methods in Its operations, i.e. maritime piracy and armed robbery, are adapting to the new economic and political reality, taking advantage of the opening of the borders to free trade and the global economy. This means that appropriate solutions must be found to reduce the impact of these crimes and address them by all international means and methods through cooperation between countries through strengthening and tightening security guards at borders. And he, in turn, will reduce the severity of this crime further by concluding agreements and treaties that operate in a tight security manner with methods calling for the elimination of pirates and piracy."
Keywords: جريمة القرصنة -- المجتمعات الإنسانية -- التجارة الدولية -- القرصنة البحرية